2018
DOI: 10.1017/wet.2018.15
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Quizalofop-p-ethyl and Acetolactate Synthase–Inhibiting Herbicides in Acetyl-coA Carboxylase Inhibitor–Resistant Rice Production

Abstract: A field study was conducted in 2015 and 2016 at the H. Rouse Caffey Rice Research Station (RRS) to evaluate antagonistic, synergistic, or neutral interactions of quizalofop when mixed with ALS-inhibiting herbicides labeled in rice production. Quizalofop was applied at 120 g ai ha−1. Mixture herbicides included penoxsulam at 40 g ai ha−1, penoxsulam+triclopyr at 352 g ai ha−1, halosulfuron at 53 g ai ha−1, bispyribac at 34 g ai ha−1, orthosulfamuron+halosulfuron at 94 g ai ha−1, orthosulfamuron+quinclorac at 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
66
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(72 citation statements)
references
References 45 publications
6
66
0
Order By: Relevance
“…Quizalofop inhibits acetyl coenzyme A carboxylase (ACCase), with postemergence activity on annual and perennial grass species [13,14]. Producers can use ACCaseresistant rice (ACCase-R) to manage weedy rice and other grass species during cultivated rice production [15]. Rotation of herbicides and herbicide mixtures with differing sites of action is important for sustainable rice production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quizalofop inhibits acetyl coenzyme A carboxylase (ACCase), with postemergence activity on annual and perennial grass species [13,14]. Producers can use ACCaseresistant rice (ACCase-R) to manage weedy rice and other grass species during cultivated rice production [15]. Rotation of herbicides and herbicide mixtures with differing sites of action is important for sustainable rice production.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase weed control, herbicide mixtures have proven to be beneficial by increasing weed control spectrum, increasing the yield and economic returns [16][17][18][19][20]. Herbicide mixtures may exhibit three responses: synergistic, antagonistic, or neutral [15,[21][22][23][24][25][26][27][28]. A neutral response occurs when the observed control is equivalent to the expected control calculated using Colby's response [15,21,23,24,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Provisia™ rice exhibits enhanced tolerance to herbicides that inhibit ACCase, allowing POST applications of quizalofop, an ACCase-inhibiting herbicide (Burton et al 1989;Focke and Lichtenthaler 1987;Rustom et al 2018). Quizalofop was first registered for use in soybean [Glycine max (L.) Merr.]…”
Section: Introductionmentioning
confidence: 99%
“…Quizalofop has historically been used for weedy rice management in soybean production at rates from 35 to 84 g ai ha −1 (Askew et al 1998;Minton et al 1989). The targeted quizalofop application rate in ACCase-R production is 92 to 155 g ai ha −1 , not to exceed 240 g ha −1 per year (Rustom et al 2018(Rustom et al , 2019.…”
mentioning
confidence: 99%
“…Herbicide antagonism is defined as "an interaction of two or more chemicals such that the effect when combined is less than the predicted effect based on each chemical applied separately" (Beste 1983:515). ACCase-inhibiting herbicide activity has a history of antagonism when co-applied with other herbicides (Barnwell and Cobb 1994;Blackshaw et al 2006;Osterholt et al 2019;Rustom et al 2018Rustom et al , 2019Vidrine et al 1995;Webster et al 2019;Zhang et al 2005). Rustom et al (2018) reported antagonism of quizalofop for weedy rice and barnyardgrass control in ACCase-R rice production when treated with mixtures of quizalofop plus acetolactate synthase-inhibiting herbicides such as halosulfuron, orthosulfamuron, imazosulfuron, bensulfuron, penoxsulam, or bispyribac-sodium.…”
mentioning
confidence: 99%